Genotype X Environment Interaction for Selected Characters from R1 Up to R5 Reproductive Stage in Soybean - Agung Karuniawan; H. C. Becker; W. Link; F. Rumawas (Zuriat, 1998)
Field Experiments were conducted to study the genotype x environment interaction for selected characters between anthesis and beginning of seed growth in soybean. The genotype. I.e. three parental lines and seven F8 offsprings were planted just before a wet season in two locations: at Kendalpayak-Malang and at Muneng-Probolinggo. Both locations belong to Research Institute for Legume and Tuber Crops and are located in East Java, Indonesia. The Reproductive growth stages were defined according to Fehr and Caviness. The evaluation started with begin of flowering (R1). Total leaf chlorophyll content, leaf area index, specific leaf weight, and biomass were measured at begin of seed growth (R5). Significant genotype X environment interactions were observed for all characters studied except for specific leaf weight.